2015
DOI: 10.18632/oncotarget.4424
|View full text |Cite
|
Sign up to set email alerts
|

High expression of XPA confers poor prognosis for nasopharyngeal carcinoma patients treated with platinum-based chemoradiotherapy

Abstract: In this study, we tried to explore if xeroderma pigmentosum complementation group-A (XPA) expression is likely a prognostic prediction factor for locally advanced nasopharyngeal carcinoma (NPC) patients treated with platinum-based chemoradiotherapy, which was considered to bring chemotherapy-related severe toxicity compared with radiotherapy alone. Firstly, MTT assay revealed that downregulating XPA expression in NPC HONE1 and CNE1 cells decreased IC50 of cisplatin and sensitized cells to cisplatin. XPA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Therefore, it is likely that upregulation of XPA expression would increase platinum resistance. Indeed, XPA expression has been reported to correlate with the resistance of nasopharyngeal carcinoma and lung cancer cell lines to platinum-based therapy (17,18,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is likely that upregulation of XPA expression would increase platinum resistance. Indeed, XPA expression has been reported to correlate with the resistance of nasopharyngeal carcinoma and lung cancer cell lines to platinum-based therapy (17,18,25).…”
Section: Discussionmentioning
confidence: 99%
“…The xeroderma pigmentosum complementation group A (XPA) protein is an indispensable factor for NER. Several reports have shown that XPA recognizes and verifies DNA damage sites, stabilizes repair intermediates, and contributes to the induction of other NER-associated factors (19)(20)(21)(22)(23)(24) (17)(18)(19)(20)(21)(22)(23)(24)(25). However, the role of XPA in the response of uterine cervical cancer cell lines and uterine cervical cancer patients to cisplatin is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Real-time quantitative PCR (qPCR) analysis was conducted as described previously [23]. Briefly, total RNA was extracted with Trizol Reagent (Invitrogen), reversely transcribed into cDNA with M-MLV reverse transcriptase (Promega, Madison, WI, USA), and sequentially subjected to qPCR analysis with the SYBR Green PCR Kit (Invitrogen) using primers shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…1a) and the percentage of corresponding positive area (P 1 -P 3 ) were evaluated by two pathologists who were blinded to clinical parameters. The ASB3 protein levels were presented as H score: H score = I 1  × P 1  + I 2 × P 2  + I 3  × P 3 [23, 28, 29]. …”
Section: Methodsmentioning
confidence: 99%
“…In the past, prognosis was a reduced life expectancy as a result of skin cancers or neurological complications [7]. However according to recent research, normal lifespan is possible for patients without neurological problems who are cautious about exposure to UV and protecting the skin.…”
Section: Short Communicationmentioning
confidence: 99%